STUDI TIPE BATUAN DAN PEMODELANNYA DI BLOK X, CEKUNGAN BARITO - Zurisman Fitriadi; Dwiharso Nugroho; Nurcahyo Indro Basuki (Bulletin of Geology, 2017)
Field X is an oilfield in Barito Basin, South Kalimantan, which produces hydrocarbon from reservoir within Lower Tanjung Formation. The oil discovery in this field was initiated in 1930 by BPM and until now Tanjung field is still productive and field development is ongoing. Layer D is in Lower Tanjung Formation and is believed as meandering channel depositional setting. Core and thin section data from Layer D could be found from well X-109, X-104, and X-105. Analysis which has been conducted finding 9 lithofacies’, including (1) siltstone-claystone (F), (2) rooted siltstone (Fr), (3) very fine sandstone (Svf), (4) fine sandstone (Sf), (5) bioturbated and rooted fine sandstone (Sfbr), (6) weakly cemented fine sandstone (Sfwc), (7) weakly cemented medium sandstone (Smwc), (8) moderately cemented medium sandstone (Smmc), and (9) coarse sandstone (Sc). These lithofacies’ are grouped into four architectural facies’ (1) channel sand, (2) point bar, (3) crevasse splay, dan (4) overbank. Rock type determination used flow zone indicator (FZI) method found 3 rock types (RT). RT 1 is associated to channel sand, RT 2 is associated to channel body, point bar, and overbank, and RT 3 is associated to channel sand, point bar, crevasse splay, and overbank. Reservoir properties modelling which is controlled by facies and rock type models showed relation in petrophysical behaviour to its rock type. High porosity values are associated to channel sand. High permeability values are associated to rock type RT 1 and RT 2.